A review of planetary roller screw mechanism for development and new trends. (November 2022) - Wu, Linping; Ma, Shangjun; Fu, Xiaojun; Zhang, Jianxin; Liu, Geng
With the rapid development of all electric mechanical equipment in the fields of industrial application, aerospace engineering, and national defense, planetary roller screw mechanism has attracted much attention as a new type actuator of electro-mechanical actuator system. This report systematically reviews previous large number of researches as well as new advancements on five types of planetary roller screw mechanisms from both available literatures and studies presented. Firstly, the general structure, merits, limitations, and the application of five types of planetary roller screw mechanisms are summarized. Then, the development state of the planetary roller screw mechanisms is elaborated in the three aspects: parameter design, contact properties, and performance analysis. Common problems and tendencies of theoretical analysis and calculation models are analyzed. Finally, the research directions and methods in the future on planetary roller screw mechanism are discussed. Key technologies and research challenges are presented in terms of multi-pair dynamic contact and multi-body vibration of system, and the development prospects for various planetary roller screw mechanisms in all electric mechanical equipment are summed up.